2006
DOI: 10.1111/j.1600-6143.2006.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Incompatible Kidney Donor Candidates´ Willingness to Participate in Donor-Exchange and Non-directed Donation

Abstract: Although paired donation, list donation and nondirected donation allow more recipients to receive living donor transplants, policy makers do not know how willing incompatible potential donors are to participate. We surveyed 174 potential donors ruled out for ABO-incompatibility or positive cross-match about their participation willingness. They were more willing to participate in paired donation as compared to list donation where the recipient receives the next deceased donor kidney (63.8% vs. 37.9%, p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
2
26
1
Order By: Relevance
“…8 In one study, the incompatible kidney donor candidates showed more willingness for KPD versus list exchanges. 9 Extrapolating these levels of willingness nationally, 1-11% (84-711 more transplants) increase in living donation rates yearly may be possible if donor-exchange programs were available nationwide. 8 It has been estimated that an additional 1000-2000 transplants per year could be accomplished if a national KPD program was implemented in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…8 In one study, the incompatible kidney donor candidates showed more willingness for KPD versus list exchanges. 9 Extrapolating these levels of willingness nationally, 1-11% (84-711 more transplants) increase in living donation rates yearly may be possible if donor-exchange programs were available nationwide. 8 It has been estimated that an additional 1000-2000 transplants per year could be accomplished if a national KPD program was implemented in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the concept of this exchange of kidneys was felt to possibly assign a value to an organ, which is not allowed under the National Organ Before a nationwide program could be established, several issues with exchanges between patients at different centers need to be settled. These include the level of workup needed before a 'pair' is entered into the database for matching; the logistics (and willingness) of donors and recipients to travel, and of centers to ship kidneys (12); the issue of dealing with levels of comfort on the part of various programs with proceeding with a given transplant; and lastly how to handle the added expense and manpower needed to allow such a complex program to run efficiently. The role of paired donation over list-paired donation schemes is also a controversial point that has an effect not only on the success of paired exchanges, but also on waiting times for deceased donor recipients, especially in blood group O.…”
Section: Paired Kidney Exchangementioning
confidence: 99%
“…Sirs, We read with great interest the report by Ferrari P, et al [1] Recent study results are valuable for encouraging participation of kidney paired donation (KPD) pairs and transplant centers in national KPD program [1][2][3][4][5][6][7]. We believe that with some additions scientific value and contribution of the article may result into wider implementation of KPD.…”
mentioning
confidence: 90%
“…In one study the incompatible kidney donor candidates' showed more willingness for KPD versus list exchanges [7]. Extrapolating these levels of willingness nationally; 1-11% increase in living donation rates yearly may be possible if donor-exchange programs were available nationwide [7]. Comparatively short waiting time in KPD [1] will save the cost of maintenance dialysis and associated morbidity and mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation